Answer ক. দেওয়া আছে, `a + b = sqrt(7), a - b = sqrt(5)`
আমরা জানি,`2(a^2 + b^2) = (a + b)^2 + (a - b)^2`
`= (sqrt(7))^2 + (sqrt(5))^2`
`= 7 + 5 = 12`
`:. a^2 + b^2 = 6` (Ans)
খ. `a^2 + b^2 = 6` [(ক) হতে পাই]
এখন, `8ab(a^2 + b^2) = 4ab.2(a^2 + b^2)`
`= {(a + b)^2 - (a - b)^2} 2.6`
`= {(sqrt(7))^2 - (sqrt(5))^2}.12`
`= (7 - 5).12 = 24`
`:. 8ab (a^2 + b^2) = 24`
গ. দেওয়া আছে,
`a + b = sqrt(7)`............(i)
`a - b = sqrt(5)`.............(ii)
`:. (a + b) (a - b) = sqrt(7) xx sqrt(5)`
বা, `a^2 - b^2 = sqrt(35)`
সমীকরণ (i) ও (ii) যোগ করে পাই,
`a + b + a - b = sqrt(7) + sqrt(5)`
বা, `2a = sqrt(7) + sqrt(5)`
`:. a = (sqrt(7) + sqrt(5))/2`
এখন, `(a - b)^3 + (a + b)^3 + 6a(a^2 - b^2)`
`= (sqrt(5))^3 + (sqrt(7))^3 + 6((sqrt(7) + sqrt(5))/2) (sqrt(35))`
`= 5sqrt(5) + 7sqrt(7) + 3sqrt(245) + 3sqrt(175)`
`= 5sqrt(5) + 7sqrt(7) + 21sqrt(5) + 15sqrt(7)`
`= 22sqrt(7) + 26sqrt(5)` (Ans)